The "Backwards, Forwards and Sideways" Changes of Ict: Ethicomp 2010: Proceedings of the Eleventh International Conference - International Conference on the Social and Ethical Impacts of Information and Communication Technologies (11th : Universitat Rovira i Virgili, Tarragona; Arias-Olive, Mario; Bynum, Terrell Ward; Rogerson, Simon; Torres-Coronas, Teresa; Centre for Computing and Social Responsibility (Universitat Rovira i Virgili, 2010)
"The purpose of this series is to provide an inclusive European forum for discussing the ethical and social issues associated with the development and application of Information and Communication Technology (ICT). The conferences are held every 18 months."--Introduction.
Keywords: Congresses; Congresses; Information technology; Information technology; Moral and ethical aspects; Professional ethics; dept.phi; faculty_collection

Oedipus: The Most Crucial Concept in Psychoanalysis - Nasio, Juan-David (SUNY series in contemporary French thought, 2010)
In this work, the author argues that the Oedipus complex represents the core of psychoanalysis as well as the fundamental constitution of the human being.--(Source of description unspecified.)
Keywords: Oedipus complex; Psychoanalysis; Oedipus Complex; Psychoanalytic Therapy; dept.phi; faculty_collection

Pornography As Simulation - Bach, T. (Porn - Philosophy for Everyone, 2010)
Keywords: Folk-psychological prowess, on MTV's The Hills; Mental simulation, and the "off-line" heuristic; Modern perversion of mental simulation; Money, lesbians and woodsmen; Philosophers and psychologists, "theory-theory" approach to folk psychology; Pornography as simulation; Simulating a day at the office; Tools of folk psychology-human beings, are prolific psychologists; World of actual sexual relationships-dangerous sexually transmitted diseases, more lethal than ever; dept.phi; origin of simulation-pornographic appropriation of mind-reading skill, and mentalizing ability

Foreword - Bynum, T.W. (Ethical Issues and Social Dilemmas in Knowledge Management: Organizational Innovation, 2010)
Keywords: dept.phi

Jokers on the mountain: In defense of gratuitous risk - Lockwood, H.H. (Climbing - Philos. for Everyone: Because It's There, 2010)
Keywords: "Jokers on the Mountain"; "The Outside Prognosticator: Really Quite Stupid"; Dan Osman's new game of controlled falling as a "Stupid Pastime"; Maria Coffey's book, Where the Mountain Casts Its Shadow; Mountaineering: The Freedom of the Hills; The Rule of Rescue; The predecessor of the so-called "Beacon Bill"; dept.phi

Coercion, inequality and the international property regime - Cavallero, Eric (Journal of Political Philosophy, 2010)
Keywords: dept.phi

Philosophy in the Information Age - Bynum, Terrell Ward (Metaphilosophy, 2010)
Abstract: In the past, major scientific and technological revolutions, like the Copernican Revolution and the Industrial Revolution, have had profound effects, not only upon society in general, but also upon Philosophy. Today's Information Revolution is no exception. Already it has had significant impacts upon our understanding of human nature, the nature of society, even the nature of the universe. Given these developments, this essay considers some of the philosophical contributions of two “philosophers of the Information Age”—Norbert Wiener and Luciano Floridi—with regard to the nature of the universe, human nature, the nature of society, and the nature of “artificial agents” such as robots, softbots, and cyborgs.
Keywords: Artificial agents; Cybernetics; Cyborgs; Digital physics; Entropy; Inforg; Information; Information Age; Information Revolution; Information age; Information revolution; Infosphere; Luciano Floridi; Norbert Wiener; Qubits; Robots; Second law of thermodynamics; artificial agents; cybernetics; cyborgs; dept.phi; digital physics; entropy; inforg; information; infosphere; qubits; robots; second law of thermodynamics

Commodification and privacy: a Lockean perspective. - Volkman, Richard (HEC forum : an interdisciplinary journal on hospitals' ethical and legal issues, 2010)
This paper defends the thesis that privacy as a right is derived from fundamental rights to life, liberty, and property and does not permit restricting the commodification of bodily material; however, privacy as life, liberty, property does require conventions that ensure a robust and just market in bodily material. The analysis proceeds by defending a general commitment to liberty and markets, but not in the manner one might expect from a 'doctrinaire' libertarian. Ethical concerns about commodification are legitimate in the context of new medical and information technologies, but these concerns are not sufficiently well defined to justify political conclusions, since not every ethical concern is in itself a political concern, and the best way to resolve certain ethical difficulties is to draw up political boundaries that facilitate the discovery and testing of various solutions to our ethical puzzles. To illustrate the point, I will indicate how privacy as life, liberty, property defines such a dynamic solution to the problems of commodification of human bodily material and slippery information in insurance markets.
Keywords: *Ownership; *Privacy; Civil Rights; Commerce; Commodification; Human Body; Humans; John Locke; Liberalism; Markets; Natural rights; Ownership; Politics; Privacy; art; article; civil rights; commercial phenomena; dept.phi; human; organization and management; politics; privacy

Why information ethics must begin with virtue ethics - Volkman, Richard (Metaphilosophy, 2010)
The information ethics (IE) of Floridi and Sanders is evaluated here in the light of an alternative in virtue ethics that is antifoundationalist, particularist, and relativist in contrast to Floridi's foundationalist, impartialist, and universalist commitments. Drawing from disparate traditional sources like Aristotle, Nietzsche, and Emerson, as well as contemporary advocates of virtue ethics like Nussbaum, Foot, and Williams, the essay shows that the central contentions of IE, including especially the principle of ontological equality, must either express commitments grounded in the particular perspectives we already inhabit, or be without rational or ethical force for us. © 2010 Metaphilosophy LLC and Blackwell Publishing Ltd.
Keywords: Ethical individualism; Foundationalism; Information ethics; Particularism; Virtue ethics; dept.phi